Novel Three-Dimensional and Biocompatible Lift-Off Method for Selective Metallization of a Scleral Contact Lens Electrode for Biopotential Detection - Schumayer, Sven; Simon, Nicolai; Sittkus, Benjamin; Wagner, Sandra; Bucher, Volker; Strasser, Torsten (Frontiers in Medical Technology, 2022)
Presbyopia describes the eye’s physiological loss of the ability to see close objects clearly. The adaptation to different viewing distances, termed accommodation, is achieved by a change in the curvature of the eye lens induced by the ciliary muscle. A possible approach to correct presbyopia could be to detect the ciliary muscle’s neuromuscular signals during accommodation and transfer these signals electronically to a biomimetic, micro-optical system to provide the necessary refractive power. As a preliminary step towards such a described system, a novel three-dimensional and biocompatible lift-off method was developed. In addition, the influence of the distance between the electrically conducting surfaces of the lens on the accommodated signal amplitudes was investigated. Compared to the conventional masking methods, this process has the advantage that three-dimensional surfaces can be masked with biocompatible gelling sugar by utilizing a direct writing process with a dispensing robot. Since gelling sugar can be used at room temperature and is water-soluble, the process presented is suitable for materials that should not be exposed to organic solvents or excessively high temperatures. Apart from investigating the shrinkage behavior of the gelling sugar during the physical vapor deposition (PVD) coating process, this paper also describes the approaches used to partially coat a commercial scleral contact lens with an electrically conductive material. It was shown that gelling sugar withstands the conditions during the PVD processes and a successful lift-off was performed. To investigate the influence of the spacing between the electrically conductive regions of the contact lens on the measured signals, three simplified electrode configurations with different distances were fabricated using a 3D printer. By testing these in an experimental setup, it could be demonstrated that the distance between the conductive surfaces has a significant influence on the amplitude. Regarding the described lift off process using gelling sugar, it was found that the dispensing flow rate has a direct influence on the line uniformity. Future work should address the influence of the viscosity of the gelling sugar as well as the diameter of the cannula. It is assumed that they are the prevailing limitations for the lateral resolution.